Existence of Pseudo Almost Automorphic Solutions to a Nonautonomous Heat Equation - Toka Diagana (Cubo, 2011)
In this paper, upon making some suitable assumptions, we obtain the existence of pseudo-almost automorphic solutions to a nonautonomous heat equation with gradient coefficients. En este trabajo, al hacer algunos supuestos adecuados, se obtiene la existencia de pseudo soluciones automorfas a una ecuacin del calor no autnoma con coeficientes degradados.